2022
DOI: 10.1002/jmv.27669
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of serum metabolites associated with infection and severity of patients with acute hepatitis E infection

Abstract: Dynamic changes in metabolites may affect liver disease progression, and provide new methods for predicting liver damage. We used ultra-performance liquid chromatography-mass spectroscopy to assess serum metabolites in healthy controls (HC), and patients with acute hepatitis E (AHE) or hepatitis E virus acute liver failure (HEV-ALF). The principal component analysis, partial least squares discriminant analysis, and discriminant analysis of orthogonal projections to latent structures models illustrated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Gut microbiota and its metabolites was recently found to be involved in the change of immune system, may participating in the development of HEV-ALF [24] . Moreover, several studies also focused on the diagnostic and prognostic markers of HEV-ALF, which indicated that low platelets and dynamic changes of serum metabolites may associated with the severity of HEV infection and prognosis of HEV-ALF [25][26][27] . Current treatment strategies for HEV-ALF usually involve fundamental supporting critical care, arti cial liver support and liver transplantation, which often cause high medical expenditure and usually not available in resource limited regions [1,10] .…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota and its metabolites was recently found to be involved in the change of immune system, may participating in the development of HEV-ALF [24] . Moreover, several studies also focused on the diagnostic and prognostic markers of HEV-ALF, which indicated that low platelets and dynamic changes of serum metabolites may associated with the severity of HEV infection and prognosis of HEV-ALF [25][26][27] . Current treatment strategies for HEV-ALF usually involve fundamental supporting critical care, arti cial liver support and liver transplantation, which often cause high medical expenditure and usually not available in resource limited regions [1,10] .…”
Section: Discussionmentioning
confidence: 99%
“…Definition of HEV‐ALF: (1) abnormal liver function (prothrombin activity ≀40% or international normalized ratio [INR] ≄1.5), jaundice and hepatic atrophy in 2 weeks; (2) stage 2 or 3 encephalopathy complicating end‐stage disease; and (3) without chronic liver disease. Exclusion criteria: (1) co‐infection with other hepatitis virus, and/or human immunodeficiency virus (HIV); (2) with other liver disease not caused by viral hepatitis; (3) incomplete data 20,21 …”
Section: Methodsmentioning
confidence: 99%
“…of genetic and genomic research, molecular diagnostic techniques focused on nucleic acid detection have provided new methods for the diagnosis of infectious diseases, with a short turnaround time and high sensitivity. Molecular diagnostic techniques can not only detect multiple pathogens, but can also analyze drug resistance genes of pathogens and pathogen homology analysis, and have gradually become an important tool in the early diagnosis of infectious diseases (10)(11)(12). At present, the commonly used molecular diagnostic techniques for infectious diseases include PCR, isothermal amplification reaction, gene chip technology and high-throughput sequencing technology.…”
Section: Advances In the Application Of Molecular Diagnostic Techniqu...mentioning
confidence: 99%
“…NASBA is an efficient, isothermal amplification method developed by Compton in 1991 (73). The amplification reaction was performed at 41˚C, and the 100-to 250-bp nucleic acid target sequence was amplified ~10 12 times within 90 min (74). The NASBA reaction mixture involves three enzymes, T7 RNA polymerase, RNase H and avian myeloblast virus reverse transcriptase, which selectively and rapidly amplify RNA in the presence of background DNA, with good sensitivity, making NASBA most suited for the analysis of RNA samples (Fig.…”
Section: Isothermal Amplificationmentioning
confidence: 99%